Development and Validation of a High-Performance Liquid Chromatography–Tandem Mass Spectrometry Method for the Simultaneous Determination of Irinotecan and Its Main Metabolites in Human Plasma and Its Application in a Clinical Pharmacokinetic Study - Marangon, Elena; Posocco, Bianca; Mazzega, Elisa; Toffoli, Giuseppe (PLOS ONE, 2015)
Irinotecan is currently used in several cancer regimens mainly in colorectal cancer (CRC). This drug has a narrow therapeutic range and treatment can lead to side effects, mainly neutropenia and diarrhea, frequently requiring discontinuing or lowering the drug dose. A wide inter-individual variability in irinotecan pharmacokinetic parameters and pharmacodynamics has been reported and associated to patients’ genetic background. In particular, a polymorphism in the UGT1A1 gene (UGT1A1*28) has been linked to an impaired detoxification of SN-38 (irinotecan active metabolite) to SN-38 glucuronide (SN-38G) leading to increased toxicities. Therefore, therapeutic drug monitoring of irinotecan, SN-38 and SN-38G is recommended to personalize therapy. In order to quantify simultaneously irinotecan and its main metabolites in patients’ plasma, we developed and validated a new, sensitive and specific HPLC–MS/MS method applicable to all irinotecan dosages used in clinic. This method required a small plasma volume, addition of camptothecin as internal standard and simple protein precipitation. Chromatographic separation was done on a Gemini C18 column (3 μM, 100 mm x 2.0 mm) using 0.1% acetic acid/bidistilled water and 0.1% acetic acid/acetonitrile as mobile phases. The mass spectrometer worked with electrospray ionization in positive ion mode and selected reaction monitoring. The standard curves were linear (R2 ≥0.9962) over the concentration ranges (10–10000 ng/mL for irinotecan, 1–500 ng/mL for SN-38 and SN-38G and 1–5000 ng/mL for APC) and had good back-calculated accuracy and precision. The intra- and inter-day precision and accuracy, determined on three quality control levels for all the analytes, were always <12.3% and between 89.4% and 113.0%, respectively. Moreover, we evaluated this bioanalytical method by re-analysis of incurred samples as an additional measure of assay reproducibility. This method was successfully applied to a pharmacokinetic study in metastatic CRC patients enrolled in a genotype-guided phase Ib study of irinotecan administered in combination with 5-fluorouracil/leucovorin and bevacizumab.